Relationship Between Customs and Religion in Minangkabau Society Shown in The Works of Hamka - Ahmad Bahtiar; Ummi Kultsum; Reza Anis Maulidya; Syihaabul Hudaa; Carole Lelievre (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2024)
The Minangkabau community, known for its devout religiosity, is unique in its adherence to a matrilineal kinship system, which differs from the patrilineal teachings of Islam. This article explains the relationship between customary law, Islam, Minangkabau society in Hamka's works.The findings not only show how the relationship between customs and religion manifest themselves in Minangkabau society, as shown in the works that are the subject of this study, but also include a critique of this relationship. Hamka argues through his works that the relationship embodied in the Minangkabau concept, namely syarak bersanding adat, adat bersanding kitabullah (religion alongside custom, custom alongside the Book of Allah), is not yet an ideal concept because it is not dominated by Sharia. As a result, the customary system still leads to discrimination, not only against outsiders but also among community members themselves, regarding the regulation of marriage and inheritance